Application of Problem Based Learning Model with Mind Mapping Method to Improve Activeness And Students Learning Outcomes of XI TKJ 2 in Network System Administration - Dwi Nurnaeni; Agus Effendi; Endar Suprih Wihidayat (Pendidikan Teknik Informatika dan Komputer, Universitas Sebelas Maret, 2021)
This research aims to improve the results of activeness and learning outcomes Network System Administration through the application of Problem Based Learning Model with Mind Mapping method grade XI student TKJ SMK N 1 Sukoharjo. This research is a class action research (PTK). The study was conducted in two cycles consisting of four phases: planning, implementation, observation, and reflection. The subject in this study is a grade XI student TKJ SMK N 1 Sukoharjo which amounted 35 students. The data collection techniques used are tests, observations, interviews, and documentation. Data validity test techniques use data source triangulation techniques and triangulation methods. Data analysis techniques use quantative descriptive analysis models. Based on the results of the research, it is important to know that the implementation of Problem Based Learning’s model with Mind Mapping method can improve the results of activeness and learning outcomes Network System Administration in XI-grade students of TKJ SMK N 1 Sukoharjo. Such improvement can be proved by increasing cognitive, affective, and psychomotor values at each of its cycles. on average the student’s cognitive test scores were 66.09 with a percentage of 31.43%. The student’s affective value of 68.75 can be categorized less, while the percentage of the affective distance is 61.43%. On average, the student’s psychomotor value is 74.9, the percentage of student’s psychomotor submission reaches 62.86%. The percentage of the activeness student’s is 65% can be categorized less. On the I cycle, the average cognitivevalue of students reaches 75.57 with a percentage of the 71.43% compensation. The average psychomotor value reaches 80, the percentage of student’s satisfaction is 74.28%, while the affective value reached 75 can be categorized well with a percentage of the compensation of 73.57%, and the percentage of the activeness student’s 77.24%. In cycle II, the cognitive average value increases to 83.42 with a percentage of the 88.57%, while the affective average value increased to 87.5 can be categorized very well with a percentage of the compensation of 82.86% and the average value psychomotor increased to 83.33, student’s submission value was 88.57%. and the percentage of the activeness student’s 82,14%. The conclusion in this study is the application of Problem Based Learning’s model with Mind Mapping method can improve the results of activeness and learning outcomes Network System Administration XI students of TKJ SMK 1 Sukoharjo.